Oncostatin M triggers brain inflammation by compromising blood-brain barrier integrity - Hermans, Doryssa; Houben, Evelien; Baeten, Paulien; Slaets, Helena; Janssens, Kris; Hoeks, Cindy; Hosseinkhani, Baharak; Duran, Gayel; Bormans, Seppe; Gowing, Elizabeth; Hoornaert, Chloé; Beckers, Lien; et al. (Acta neuropathologica, 2022)
Oncostatin M (OSM) is an IL-6 family member which exerts neuroprotective and remyelination-promoting effects after damage to the central nervous system (CNS). However, the role of OSM in neuro-inflammation is poorly understood. Here, we investigated OSM’s role in pathological events important for the neuro-inflammatory disorder multiple sclerosis (MS). We show that OSM receptor (OSMRβ) expression is increased on circulating lymphocytes of MS patients, indicating their elevated responsiveness to OSM signalling. In addition, OSM production by activated myeloid cells and astrocytes is increased in MS brain lesions. In experimental autoimmune encephalomyelitis (EAE), a preclinical model of MS, OSMRβ-deficient mice exhibit milder clinical symptoms, accompanied by diminished T helper 17 (Th17) cell infiltration into the CNS and reduced BBB leakage. In vitro, OSM reduces BBB integrity by downregulating the junctional molecules claudin-5 and VE-cadherin, while promoting secretion of the Th17-attracting chemokine CCL20 by inflamed BBB-endothelial cells and reactive astrocytes. Using flow cytometric fluorescence resonance energy transfer (FRET) quantification, we found that OSM-induced endothelial CCL20 promotes activation of lymphocyte function-associated antigen 1 (LFA-1) on Th17 cells. Moreover, CCL20 enhances Th17 cell adhesion to OSM-treated inflamed endothelial cells, which is at least in part ICAM-1 mediated. Together, these data identify an OSM-CCL20 axis, in which OSM contributes significantly to BBB impairment during neuro-inflammation by inducing permeability while recruiting Th17 cells via enhanced endothelial CCL20 secretion and integrin activation. Therefore, care should be taken when considering OSM as a therapeutic agent for treatment of neuro-inflammatory diseases such as MS.
Gesehen am 23.10.2023